The place of modern α-2-agonists in the intraoperative sedation of trauma / orthopedic patients - A Domoratskiy; V Kryliuk; I Kuchynska; T Pylypenko; A Pavlenko; D Horban (Perioperative Medicine, 2020)
Modern traumatological operations have a number of features: duration, a large pool of age-related patients with low functional reserves, forced position of the body, operations are often under regional anesthesia with a conserved consciousness, which requires special attention from the anesthesiologist. Intraoperative sedation by intravenous agents is used to prevent stress reactions associated with the effect of the patient’s presence on the operation. One of the classes is α-2 adrenergic agonists, drugs with antinociceptive, anxiolytic, sympatholytic activity, and at the same time, they have a number of side effects in the form of hypo/ hypertension, vasospasm, bradycardia. In this article the place of the modern α-2 agonist dexmedetomedine in the schemes of perioperative management of patients with skeletal injury was considered.